Size Dependence of the Band Gap of Core–Shell Tantalum and Tantalum Oxide (V) Nanoclusters - Valentin A. Shilov; Petr V. Borisyuk; Diana V. Bortko; Smagul Karazhanov; Yuri Y. Lebedinskii; Oleg S. Vasilyev (Nanomaterials)
Monodisperse films of spherical tantalum oxide (V) nanoclusters and spherical tantalum nanoclusters with a tantalum oxide shell with diameters of 1.4–8 nm were obtained by magnetron sputtering. The size of the deposited nanoclusters was controlled using a quadrupole mass filter. The chemical composition was certified using the XPS method. Using the Reflected Electron Energy Loss Spectroscopy (REELS), the dependence of the band gap width on the nanocluster size was determined. It was found that starting from a certain nanocluster size, the band gap width increases as the nanocluster size decreases. Based on experimental data and a theoretical model, the effective mass of electrons dependence as a function of nanocluster size was obtained.